Web-Based New Student Admission System using the Rapid Application Development (RAD) Method at Penraujan Private Junior High School - Dwi Muazarah; Barany Fachri; Abdul Khaliq (SEAN Institute, 2026)
The advancement of information technology has significantly influenced the education sector, particularly in the management of new student admissions. Many schools still rely on manual registration processes that are time-consuming, prone to data entry errors, and inefficient in managing applicant data. Penraujan Private Junior High School is one of the institutions that continues to use a conventional registration system, resulting in administrative difficulties, especially during periods of increased enrollment. This study aims to develop a web-based new student admission system to improve the efficiency, accuracy, and accessibility of the registration process. The system enables prospective students to register online at any time and assists the school in managing, storing, and generating registration data and reports more effectively. The Rapid Application Development (RAD) method is applied in this research due to its emphasis on fast and iterative system development while accommodating user needs. The results of this study indicate that the proposed web-based admission system is able to streamline the registration process, reduce data input errors, and enhance the quality of administrative services at Penraujan Private Junior High School. This system also provides convenience for prospective students by allowing online registration without the need to visit the school directly.